2013
DOI: 10.1139/cjfr-2012-0367
|View full text |Cite
|
Sign up to set email alerts
|

Fire emissions estimates in Siberia: evaluation of uncertainties in area burned, land cover, and fuel consumption

Abstract: Boreal forests constitute the world's largest terrestrial carbon pools. The main natural disturbance in these forests is wildfire, which modifies the carbon budget and atmosphere, directly and indirectly. Wildfire emissions in Russia contribute substantially to the global carbon cycle and have potentially important feedbacks to changing climate. Published estimates of carbon emissions from fires in Russian boreal forests vary greatly depending on the methods and data sets used. We examined various fire and veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 38 publications
1
53
0
Order By: Relevance
“…MODIS MCD64A1 reported the smallest area burned for almost the whole year from 2000 to 2011, whereas the estimates from the combination of AVHRR and MODIS burned area product (AVHRR/MODIS) [117,118] were consistently greater than the MCD45A1 and MCD64A1 products by 6%-560% [139]. The great variation among burned area estimates in the region of Siberia have been accounted for through the instrument capabilities (e.g., resolution, cloud cover, fire types detection), differing methods of analysis and the absence of official data for the calibration and validation of burned areas [139]. These suggest that the use of global burned area products for local and regional scales should be validated and compared with other independent datasets (e.g., higher resolution datasets and official fire data) to quantify omission/commission errors.…”
Section: Remote Sensing Data and Derived Products For Burned Area Mapmentioning
confidence: 86%
See 3 more Smart Citations
“…MODIS MCD64A1 reported the smallest area burned for almost the whole year from 2000 to 2011, whereas the estimates from the combination of AVHRR and MODIS burned area product (AVHRR/MODIS) [117,118] were consistently greater than the MCD45A1 and MCD64A1 products by 6%-560% [139]. The great variation among burned area estimates in the region of Siberia have been accounted for through the instrument capabilities (e.g., resolution, cloud cover, fire types detection), differing methods of analysis and the absence of official data for the calibration and validation of burned areas [139]. These suggest that the use of global burned area products for local and regional scales should be validated and compared with other independent datasets (e.g., higher resolution datasets and official fire data) to quantify omission/commission errors.…”
Section: Remote Sensing Data and Derived Products For Burned Area Mapmentioning
confidence: 86%
“…The MCD45A1 dataset underestimated and resulted in a higher fraction of burned area compared to the GFED3 data [62]. Similarly, Kukavskaya et al [139] found that estimates of burned areas in the region of Siberia from 2000 to 2011 differed significantly and were inconsistent within the data sources. MODIS MCD64A1 reported the smallest area burned for almost the whole year from 2000 to 2011, whereas the estimates from the combination of AVHRR and MODIS burned area product (AVHRR/MODIS) [117,118] were consistently greater than the MCD45A1 and MCD64A1 products by 6%-560% [139].…”
Section: Remote Sensing Data and Derived Products For Burned Area Mapmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the central Siberian site is representative of most of central Siberian middle taiga forest with regards to climate, topography, soils and type of forest and, in recent decades, has experienced an increase in the length of the fire season and intensification of the fire regime [59]. The southern taiga location represents an area where approximately 40% of annual fires in Russia occur [60]. It also represents a region of Siberia where shifts in vegetation type associated with climate change have already been observed [28] and the increase in frequency and intensity of fires is facilitating a non-reversible (on the human time scale) shift from forest to steppe or grassland [29,60].…”
Section: Methodsmentioning
confidence: 99%